Homocysteine Levels Influence Platelet Reactivity in Coronary Artery Disease Patients Treated With Acetylsalicylic Acid. Issue 1 (July 2015) - Verdoia, Monica; Schaffer, Alon; Pergolini, Patrizia; Rolla, Roberta; Barbieri, Lucia; Bellomo, Giorgio; Sinigaglia, Fabiola; Marino, Paolo; Suryapranata, Harry; De Luca, Giuseppe
Abstract : Background: Suboptimal platelet inhibition with antiplatelet treatments is associated with a severe prognosis in patients with coronary artery disease (CAD), and the identification of its determinants is still challenging. Homocysteine elevation has emerged as a prothrombotic factor, influencing coagulative status and endothelial function and potentially modulating platelet aggregation. We therefore aimed to evaluate the effects of homocysteine (Hcy) levels on platelet reactivity in patients receiving acetylsalicylic acid (ASA) with or without ADP antagonists. Methods: Patients undergoing coronary angiography and receiving ASA (100–160 mg daily) for >7 days, with or without ADP antagonists, were included. Aggregation tests were performed by multiple electrode aggregometry. Suboptimal platelet inhibition was defined as on-treatment aggregation above the lower limit of normality. Results: Our population is represented by 508 ASA-treated patients, 406 (80.1%) of whom on dual antiplatelet therapy (ASA and ADP antagonists). Hcy levels above the median (15.1 nmol/mL) were associated with male gender ( P = 0.04), hypertension ( P = 0.004), hypercholesterolemia ( P = 0.03), aging, renal failure ( P < 0.001, respectively), previous coronary bypass grafting ( P = 0.04), therapy with calcium antagonists ( P = 0.04) and diuretics ( P = 0.001), and multivessel CAD ( P = 0.03). Higher Hcy is directly related with serum creatinine and uric acid ( P < 0.001). Suboptimal platelet inhibition was found in 16 patients (3.2%) for ASA and for ADP antagonists in 80 patients (19.7%). Hcy levels significantly affected suboptimal response to ASA, but not to ADP-mediated aggregation. In fact, a linear relationship was found between homocysteine and platelet reactivity after stimulation with arachidonic acid (r = 0.14, P = 0.004) and collagen (r = 0.12, P = 0.02), but not with ADP (r = 0.02, P = 0.77). Moreover, after correction for baseline differences, Hcy above the median was confirmed as an independent predictor of impaired ASA response [adjusted odds ratio (95% confidence interval) = 3.7 (1.08–12.4), P = 0.04]. Conclusions: Among patients with CAD, elevated homocysteine is an independent predictor of suboptimal response to ASA, but not to ADP antagonists.